Synthesis and preliminary biological evaluation of a small library of hybrid compounds based on Ugi isocyanide multicomponent reactions with a marine natural product scaffold. Issue 22 (15th November 2015) - Avilés, Edward; Prudhomme, Jacques; Le Roch, Karine G.; Franzblau, Scott G.; Chandrasena, Kevin; Mayer, Alejandro M.S.; Rodríguez, Abimael D.
Graphical abstract: Abstract: A mixture-based combinatorial library of five Ugi adducts (4 –8 ) incorporating known antitubercular and antimalarial pharmacophores was successfully synthesized, starting from the naturally occurring diisocyanide3, via parallel Ugi four-center three-component reactions (U-4C-3CR). The novel α-acylamino amides obtained were evaluated for their antiinfective potential against laboratory strains of Mycobacterium tuberculosis H37 Rv and chloroquine-susceptible 3D7 Plasmodium falciparum . Interestingly, compounds4 –8 displayed potent in vitro antiparasitic activity with higher cytotoxicity in comparison to their diisocyanide precursor3, with the best compound exhibiting an IC50 value of 3.6 nM. Additionally, these natural product inspired hybrids potently inhibited in vitro thromboxane B2 (TXB2 ) and superoxide anion (O2 − ) generation from Escherichia coli lipopolysaccharide (LPS)-activated rat neonatal microglia, with concomitant low short-term toxicity.